Outcome of Management of Walled-off Necrosis: An Experience from University Hospital of Nepal - Thapa, Pradip; Bhandari, Suyog; Sharma, Deepak; Maharjan, Narendra; Pradhan, Sumita; Kandel, Bishnu Prasad; Bhandari, Ramesh Singh; Joshi Lakhey, Paleswan (Journal of Institute of Medicine Nepal, 2024)
Introduction The patients with walled-off necrosis after acute necrotizing pancreatitis may require multiple interventions and may be associated adverse outcomes. Intensive care unit admission for organ failure and multistage step-up approaches are the cornerstones of optimal management. This study was conducted to evaluate the clinical characteristics and outcomes of the different strategies for the management of walled-off necrosis. Methods This is a retrospective cross-sectional study of the patients with walled-off necrosis, managed from July 2022 to January 2024. The demographic data, clinical parameters and outcomes of different strategies including percutaneous and endoscopic drainage and laparoscopic and open necrosectomy were analyzed. Results Twenty-five patients diagnosed with walled-off necrosis were evaluated. The mean age of those patients was 41.64±12.44 years, and 13 (52%) were females. The median time interval between the onset of acute pancreatitis and percutaneous drainage was 31 (28-42) days. Seventeen (68%) patients were managed with percutaneous transgastric drainage. Among four (16%) patients requiring step-up approach, one required endoscopic ultrasound guided drainage, two (8%) underwent open necrosectomy, one underwent laparoscopic necrosectomy. The median length of hospital stay was 16 (3-60) days. There were four (16%) mortalities, two (8%) after percutaneous drainage only, one after endoscopic ultrasound guided drainage and one after open necrosectomy, all due to sepsis and multiple organ failure. Conclusion Initial percutaneous transgastric drainage is feasible, safe and effective in the management of majority of patients with walled-off necrosis, thereby reducing further invasive interventions and improving the overall outcomes of the patients.